1980
DOI: 10.1111/j.1399-6576.1980.tb01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Surgical Patients with Verified Preoperative Myocardial Infarction

Abstract: A series of 89 surgical patients (111 operations) with preoperative myocardial infarction (MI) was analysed for factors predisposing to the development of a postoperative reinfarction. Six of them suffered postoperative MI, and three of these patients died. In the statistical analysis the following risk factors emerged: age over 60 years, anaemia, hypertension, and the fact that the previous MI had been posterior. Abdominal operations were more dangerous concerning reinfarction than other operations. In the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In fact, patients with coronary disease undergoing cardiac or noncardiac surgery are at higher risk of myocardial infarction (MI) if prolonged hypotension occurs during the procedure. [7][8][9][10] It has also been suggested that hypotension associated with CAS increases the risk of cerebrovascular events in impairing the distal washout of residual emboli not intercepted by the protection device. 2,11 The concern about the potential harmfulness of hypotension and bradycardia during or after CAS has enhanced the scientific interest about its risk factors.…”
mentioning
confidence: 99%
“…In fact, patients with coronary disease undergoing cardiac or noncardiac surgery are at higher risk of myocardial infarction (MI) if prolonged hypotension occurs during the procedure. [7][8][9][10] It has also been suggested that hypotension associated with CAS increases the risk of cerebrovascular events in impairing the distal washout of residual emboli not intercepted by the protection device. 2,11 The concern about the potential harmfulness of hypotension and bradycardia during or after CAS has enhanced the scientific interest about its risk factors.…”
mentioning
confidence: 99%
“…MI indicates myocardial infarction; NA, not applicable. Patients were stratified into 5 groups: those who experienced an initial MI 0-3 months before undergoing lumbar surgery (0-3), those who experienced an initial MI 4-6 months before undergoing lumbar surgery (4-6), those who experience an initial MI 7-12 months before surgery (7)(8)(9)(10)(11)(12), those who experienced an initial MI 13-24 months before undergoing lumbar surgery (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and those who experienced an initial MI 25+ months before undergoing lumbar surgery. MI indicates myocardial infarction; NA, not applicable.…”
Section: Resultsmentioning
confidence: 99%
“…6 While large cohort studies have demonstrated that 0.1%-0.7% of patients experience MI after surgery, 7,8 1-week postoperative reinfarction rates have been documented at rates around 7%. 9,10 Furthermore, Topkins and Artusio 8 demonstrated that patients experiencing a postoperative infarction had a mortality rate of 26.5% while patients experiencing a postoperative reinfarction had a mortality rate of 70%.…”
mentioning
confidence: 99%